Comparison of 4 Methods for Dynamization of Locking Plates: Differences in the Amount and Type of Fracture Motion. Issue 10 (October 2017) - Henschel, Julia; Tsai, Stanley; Fitzpatrick, Daniel C.; Marsh, John L.; Madey, Steven M.; Bottlang, Michael
Abstract : Background: Decreasing the stiffness of locked plating constructs can promote natural fracture healing by controlled dynamization of the fracture. This biomechanical study compared the effect of 4 different stiffness reduction methods on interfragmentary motion by measuring axial motion and shear motion at the fracture site. Methods: Distal femur locking plates were applied to bridge a metadiaphyseal fracture in femur surrogates. A locked construct with a short-bridge span served as the nondynamized control group (LOCKED). Four different methods for stiffness reduction were evaluated: replacing diaphyseal locking screws with nonlocked screws (NONLOCKED); bridge dynamization (BRIDGE) with 2 empty screw holes proximal to the fracture; screw dynamization with far cortical locking (FCL) screws; and plate dynamization with active locking plates (ACTIVE). Construct stiffness, axial motion, and shear motion at the fracture site were measured to characterize each dynamization methods. Results: Compared with LOCKED control constructs, NONLOCKED constructs had a similar stiffness ( P = 0.08), axial motion ( P = 0.07), and shear motion ( P = 0.97). BRIDGE constructs reduced stiffness by 45% compared with LOCKED constructs ( P < 0.001), but interfragmentary motion was dominated by shear. Compared with LOCKED constructs, FCL and ACTIVE constructs reduced stiffness by 62% ( P < 0.001) and 75% ( P < 0.001), respectively, and significantly increased axial motion, but not shear motion. Conclusions: In a surrogate model of a distal femur fracture, replacing locked with nonlocked diaphyseal screws does not significantly decrease construct stiffness and does not enhance interfragmentary motion. A longer bridge span primarily increases shear motion, not axial motion. The use of FCL screws or active plating delivers axial dynamization without introducing shear motion. Abstract : Supplemental Digital Content is Available in the Text.